An entertainment-education approach to prevent COVID-19 spread: study protocol for a multi-site randomized controlled trial - Vandormael, Alain; Adam, Maya; Greuel, Merlin; Bärnighausen, Till (Trials, 2020)
Entertainment-education (E-E) media can improve behavioral intent toward health-related practices. In the era of COVID-19, millions of people can be reached by E-E media without requiring any physical contact. We have designed a short, wordless, animated video about preventive COVID-19 behaviors that can be rapidly distributed through social media channels to a global audience. The E-E video’s effectiveness, however, remains unclear.